The Utility of ICD9-CM Codes in Identifying Induction of Labor - Levine, Lisa D.; Limaye, Meghana; Srinivas, Sindhu K. (American Journal of Perinatology, 2015)
Background Data evaluating the accuracy of ICD9-CM codes in identifying inductions are limited. Our objective was to examine the test characteristics of ICD9-CM coding for induction of labor and to identify differences between those captured by coding and those not.Methods We performed a retrospective cohort study of ICD9-CM codes in identifying charts of induced women at our institution from 2005 to 2009. Review of the medical record was the gold standard. Characteristics of the charts were compared using Mann–Whitney U tests and chi-square tests where appropriate.Results A total of 3,263 women were included, 708 with ICD9-CM coding for induction (screen positive). A total of 422 women were randomly sampled from those not coded as induction (screen negative). The sensitivity of ICD9-CM coding for induction was 51.4%, specificity 98.8%, positive predictive value 96.6%, negative predictive value 74.7%. False negative charts (25%) were more likely to be women induced for premature rupture of membranes (40% versus 8%, p < 0.001) or with oxytocin (51% versus 33%, p < 0.001) when compared with screen positive charts.Conclusions It is reassuring that 97% of charts coded for induction by ICD9-CM codes are, in fact, patients that were induced. With this degree of accuracy, we can be confident that charts coded as induction are unlikely to be miscoded.
Keywords: accuracy; coding; ICD9; induction of labor